Replication licensing - Blow, Julian (Henry Stewart Talks, 2009)
Problems in ensuring complete genome replication, Experiments revealing the existence of a replication licence, The licensing reaction, ORC, Cdc6, Cdt1 and Mcm2-7, Cell cycle regulation of licensing, Pre-RC substrates in yeast, Regulation of licensing in animal cells by Cdt1 degradation and geminin inhibition, Is there a licensing checkpoint?, Replication licensing and cancer, The 'MCM paradox' and dormant replication origins, The licensing system as a potential anti-cancer target